2018
DOI: 10.1097/md.0000000000011694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics associated with bone mineral density improvement after 1-year alendronate/vitamin d3 or calcitriol treatment

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The efficacy of calcitriol and calcium/Vitamin-D (caltrate) in the treatment of osteoporosis has been confirmed by many studies. 6 , 7 , 13 Calcitriol is the most active drug among the metabolites of active Vitamin-D. In a Chinese randomized control study (RCT), Zhang ZL et al 14 showed that calcitriol can improve bone metabolism factor levels in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of calcitriol and calcium/Vitamin-D (caltrate) in the treatment of osteoporosis has been confirmed by many studies. 6 , 7 , 13 Calcitriol is the most active drug among the metabolites of active Vitamin-D. In a Chinese randomized control study (RCT), Zhang ZL et al 14 showed that calcitriol can improve bone metabolism factor levels in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Tendo isso em visto, sabe-se que o cálcio e a vitamina D trabalham sinergicamente no osso. Em contrapartida, outros estudos indicam que ainda é controverso se a insuficiência de vitamina Dn com ou sem baixa ingestão de cálcio na dietan pode afetar adversamente a resposta da DMO em pacientes com osteoporose na pós-menopausa (LIAO, EY et al, 2018b).…”
Section: Discussionunclassified
“…Targeted therapy for bone metastasis aims to reduce or delay the occurrence of bone-associated events, including pathological fracture and bone pain, therefore improving the quality of life of patients and extending their survival time. Advances in the therapeutic options for the treatment of bone disease include the use of bisphosphonates (64), denosumab (65) or RANKL-antibodies that target osteoclastogenesis, which have significantly reduced the complications of bone metastasis and offered good clinical effects (6668). However, the overall survival time of patients with bone metastases has not significantly improved with these treatments (69).…”
Section: Cancer To the Bone: A Fatal Attractionmentioning
confidence: 99%